Thymic Function Impacts the Peripheral CD4/CD8 Ratio of HIV-Infected Subjects - Rosado-Sánchez, I.; Herrero-Fernández, I.; Genebat, M.; Ruiz-Mateos, E.; Leal, M.; Pacheco, Yolanda M. (Clinical infectious diseases, 2017)
Background. The persistence of an inverted CD4/CD8 ratio has been extensively associated with the increased morbimortality of chronic human immunodeficiency virus (HIV)-infected subjects. Thymic function is crucial for the maintenance of T cell homeostasis. We explored the impact of thymic function on the CD4/CD8 ratio of HIV-infected subjects. Methods. In a cohort of 53 antiretroviral-naive HIV-infected subjects, the measure of thymic volume, as a representative marker for thymic function, was available at baseline and at 12, 24, and 48 weeks post antiretroviral treatment. Results. Baseline thymic volume was associated with the CD4/CD8 ratio (ρ = 0.413, P = .002), being this association highly dependent on the CD4 T cell levels. In subjects who achieved undetectable viral load after treatment (n = 33), a higher baseline thymic volume was associated with a higher increase in CD4 T cell counts and a decreasing trend in CD8 T cell counts during follow-up. Moreover, the baseline thymic volume was independently associated with the normalization of the CD4/CD8 ratio after 96 weeks of treatment (odds ratio, 95% confidence interval: 1.95 (1.07–3.55); P = .03). Conclusions. Our data indicate the relevance of the remaining thymic function before the start of treatment to the CD4/CD8 ratio of HIV-infected subjects and, hence, potentially, in their clinical progression.